2011
DOI: 10.1603/ec10256
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Diapause Response of the Springtail Pest Sminthurus viridis (Collembola: Sminthuridae) in Southeastern Australia

Abstract: The springtail, Sminthurus viridis (L.) (Collembola: Sminthuridae), is an important agricultural pest across southern Australia. We investigated the seasonal abundance patterns and summer diapause response of S. viridis in southeastern Australia by using field and shadehouse (a greenhouse that offers seedlings shade) experiments. Seasonal activity patterns of S. viridis were largely consistent with previous studies, with the pest active from autumn to spring. In addition, the timing and pattern of the summer-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…3 By contrast, diapause is a prospective dormancy antedating environmental stress and therefore reactivation requires species-specific mechanisms. 4 Although a few species enter obligatory diapause at a specific stage in the life cycle regardless of environmental cues, 2 facultative diapause is induced in most species by abiotic factors (e.g., day length, 5,6 temperature, 7 soil moisture 8,9 ) and/or biotic factors (e.g., maturity of host plants, [9][10][11] predator-prey interactions, 12 scarcity of food 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 By contrast, diapause is a prospective dormancy antedating environmental stress and therefore reactivation requires species-specific mechanisms. 4 Although a few species enter obligatory diapause at a specific stage in the life cycle regardless of environmental cues, 2 facultative diapause is induced in most species by abiotic factors (e.g., day length, 5,6 temperature, 7 soil moisture 8,9 ) and/or biotic factors (e.g., maturity of host plants, [9][10][11] predator-prey interactions, 12 scarcity of food 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 Biotic factors such as increasing maturity of host plants can induce diapause in both winter-diapause 10,[20][21][22] and summer-diapause species. 8,9,11 Much is known about the interactions between multiple factors affecting winter diapause, 7,17,[22][23][24] however, comparatively speaking, few published studies have focused on species undergoing summer diapause. 14 Diapause can be categorized according to life stage, which in Acari can include egg, larva, nymph and adult diapause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta situación es consistente con observaciones realizadas en prados húmedos de otras latitudes (Choi et al 2006;Schäfer et al 2006;Lods-Crozet et al, 2009;Roberts et al 2011). Según Hermosilla et al (1975), Collembola es un grupo dominante en suelos de turberas, muy comunes bajo condiciones antárticas y subantárticas.…”
Section: Efecto De La Condición Hídrica De La Vegaunclassified
“…The summer aestivation is relatively short in Waikato, allowing up to five generations a year, with populations peaking in spring (October/November) (Dentener 1985). Australian research has shown hatching can continue throughout summer under irrigation (Roberts et al 2011).…”
Section: Introductionmentioning
confidence: 99%